MENAKAR FUNGSI REPRESENTASI DPRD PROVINSI BALI: STUDI KASUS PENOLAKAN DESA ADAT INTARAN TERHADAP PROYEK TERMINAL LIQUEFIED NATURAL GAS (LNG) - Muhammad Hilmi; Al Hafizh Mugi Rahmatullah; Daffa Alghifari (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2022)
There are cases where the legislature appears to be "relenting" and ignoring the people's interest in the executive because of the similarity of the background of the political party's origin. Bali Governor Wayan Koster is a cadre of PDI Perjuangan and 33 of the 55 members of the Bali Provincial Parliament come from PDI Perjuangan so that because of the similarity of political party backgrounds, it eliminates dialectics and legislative criticism that should represent the interests of the people towards executive policies that are not on the side of the people. This is a defect in the function of legislative representation. The case of rejection of the Liquefied Natural Gas (LNG) terminal project is one example of the case. This research uses a qualitative approach with data collection techniques through interviews and documentation studies. The rejection of the project arose after a discourse on moving its development position from Benoa Port to the coastal area of Sidakarya Village. This has led to rejection from various elements of the community because of the coast of Sidakarya Village, which is a mangrove area. His refusal was conveyed to the Bali Provincial Parliament through several mass actions. However, on the other hand, the Bali Provincial Legislature actually processed the revision of Regional Regulation No. 3 of 2020 concerning the Regional Spatial Plan (RTRW) requested by the Bali Provincial Government which was allegedly to accommodate the transfer of the Liquefied Natural Gas (LNG) terminal construction project.Terdapat beberapa kasus dimana legislatif terlihat “mengalah” dan mengabaikan kepentingan rakyat terhadap eksekutif karena kesamaan background asal partai politik. Gubernur Bali Wayan Koster merupakan kader PDI Perjuangan dan 33 dari 55 anggota DPRD Provinsi Bali berasal dari PDI Perjuangan sehingga karena kesamaan background partai politik, menghilangkan dialektika serta kritisisme legislatif yang seharusnya merepresentasikan kepentingan rakyat terhadap kebijakan-kebijakan eksekutif yang tidak berpihak pada rakyat. Hal tersebut menjadi sebuah kecacatan fungsi representasi legislatif. Kasus penolakan proyek terminal Liquefied Natural Gas (LNG) menjadi salah satu contoh kasusnya. Penelitian ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data melalui wawancara dan studi dokumentasi. Penolakan akan proyek tersebut muncul setelah adanya wacana pemindahan posisi pembangunannya dari Pelabuhan Benoa ke daerah pesisir Desa Sidakarya. Hal tersebut mendatangkan penolakan dari berbagai elemen masyarakat karena pesisir Desa Sidakarya yang merupakan kawasan mangrove. Penolakannya disampaikan kepada DPRD Provinsi Bali melalui beberapa aksi massa. Namun, di sisi lain DPRD Provinsi Bali justru memproses revisi Peraturan Daerah No. 3 Tahun 2020 tentang Rencana Tata Ruang Wilayah (RTRW) permintaan Pemprov Bali yang disinyalir untuk mengakomodasi pemindahan proyek pembangunan terminal Liquefied Natural Gas (LNG).